Banking: Depth Classification Version of CC - Neelameghan, A. (Journal of Information and Knowledge, 1971)
A depth classification version of Colon Classification for compound subjects going with the Basic Subject "X62 Banking" is given. The methodology of design is based on that for freely faceted classification. Two common schedules-one for "Negotiable instruments" and another for "Party"-are given for use in "Divide like" device in forming array isolates. This has helped the design to conform to the Law of Parsimony, and to the Canons of Helpful Sequence, Consistent Sequence, and Mnemonics. An index to the schedule, and thirty-two examples of subjects classified according to the depth version are given.